Technical report: modelling of blood flow in human by using Windkessel Model / Nurul Nadiah Mohammad and Amira Fairuz Adnan - Mohammad, Nurul Nadiah; Adnan, Amira Fairuz (2017)
In order to provide a platform for the maximum healthy living style, this project is done to study the blood flow into the aorta. As the main component, aorta continuously supplies the blood containing oxygen, and nutrients to all parts of the body in general. Windkessel model is used as the model to this project as Windkessel model is frequently used to represent the relation between blood flow to the aorta and blood pressure. It describes the flow of blood through the arteries as the flow of fluid through pipes. So in this project, the electrical analog is used to represent the blood flow to the aorta. This project will briefly explained about three element in Windkessel model which consist of 2-element, 3-element, and 4-element. The results plotted on graph by using MATLAB is to show the blood pressure with various initial condition and the comparison graph between 2-element and 4-element of Windkessel model.